GASTRODIPLOMASI – UPAYA MEMPERKUAT DIPLOMASI INDONESIA - Adirini Pujayanti (Jurnal Politica, 2017)
Gastrodiplomacy is cultural diplomacy that used food as a vehicle to increase brand awareness of the nation. It is an instrument for creating cross-cultural awareness in the hope to improving interaction and international cooperation. This paper demonstrates Indonesia culinary potential that can be employed as an instrument to strengthen Indonesia. The paper based on field research in Yogyakarta, Solo and Semarang argues that Indonesian gastro diplomacy has fully developed.